Hubungan antara pola konsumsi gluten dan kasein dengan skor CARS (childhood autism rating scale) pada anak ASD (autistic spectrum disorder) - Rahmawati Rahmawati; Sunartini Sunartini; Madarina Julia (Minat S2 Gizi dan Kesehatan, Prodi S2 IKM, FK-KMK UGM, 2006)
Background: The worldwide prevalence of ASD (Autistic Spectrum Disorder) during the last few years is increasing. The association between diet free of gluten and casein and improvement of autistic behaviors is still under questions.Objective: To study the association between the consump6tion of gluten and casein and the score of Childhood Autistic Rating Scale (CARS) in children with ASD (Autistic Spectrum Disorder). The study also aimed at understanding mothers’ attitude toward the diet.Methods: This was a cross sectional study on 10 mothers of children suffering from ASD in a clinic in Yogyakarta, Indonesia. A dietician measured the consumptions of gluten and casein with scored food frequency questionnaire while experts in the clinic measured CARS. In-depth interviews were performed to capture the mothers’ attitude toward the diet.Result: There was a decrease in the mean score of consumption of gluten and casein before and after diagnoses of ASD, mean difference of 156.6 (125.2; 187.9), p<0.001). There was no significant correlation between the consumption score of gluten and casein and the decrease in the score of CARS (r= 0.274, p= 0.82). Mothers thought diet free of gluten and casein was associated with improvement of behaviors.Conclusion: Consumption of gluten and casein decreased after diagnosis of ASD. Mothers think diet free of gluten and casein improved their children’s behaviors.